The psychological concerns of contemporary poets in light of the impact of the Coronapandemic ; selected models (مجلة إحالات, 2026)
This research paper aims to uncover the impact of the Corona pandemic (Covid-19) on contemporary Arabic poetry, by revealing the profound impact it has left on the hearts of contemporary poets, byhighlighting the negative and positive psychological concerns that they faced, which were the reason fortheir multiple pens in expressing this phenomenon. Jassim Al-Sahih, Esmat Radwan, Ahmed Mahdi AlHakami, Muhammad Saleh Al-Jazaeri, Nouri Siraj Al-Waeli, Abdulaziz Al-Hammami.